Pengembangan Game Edukasi Berbantuan Gimkit Berbasis Pendekatan Deep Learning Terhadap Kemampuan Pemecahan Masalah Matematis Dalam Materi Kesebangunan Pada Siswa SMP Kelas VII - Huda, Nurul; Haryadi, Rahman; Ardiawan, Yadi (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
This study aims to develop an educational game assisted by Gimkit based on a deep learning approach and to determine its feasibility from the aspects of validity, practicality, and effectiveness towards students' mathematical problem-solving abilities on the topic of similarity. The background of this study is the low ability of students in solving similarity problems and the lack of variations in interesting and motivating learning media. The method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 34 students of class VII E of SMP Negeri 1 Sungai Kakap. The results showed that the developed media had a validity level of 92.49% (very valid), practicality of 93.98% (very practical), and effectiveness of 92% (very effective) with 31 of 34 students achieving scores above the KKM. Thus, the Gimkit-assisted educational game based on a deep learning approach is deemed suitable for use as a mathematics learning medium because it has proven valid, practical, and effective in improving mathematical problem-solving skills while motivating students to think critically, creatively, and actively in the learning process. Keywords: Educational Game, Gimkit, Deep Learning, Mathematical Problem-Solving Skills, Similarity, ADDIE Model